Dynamic Upper and Lower Airway Microbiotas in Paediatric Bronchiectasis Exacerbations: A Pilot Study - Broderick, David T. J.; Regtien, Tyler; Ainsworth, Alana; Taylor, Michael W.; Pillarisetti, Naveen (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Non-cystic fibrosis bronchiectasis is a respiratory health condition with many possible aetiologies, some of which are potentially reversible in childhood with early diagnosis and appropriate treatment. It is important to understand factors which contribute to progression or potential resolution of bronchiectasis. It is evident that respiratory exacerbations are a key feature of bronchiectasis disease progression. In this pilot study we document how the microbiota of the upper and lower airways presents during the course of an exacerbation and treatment. Methods We recruited children (aged 1-15) undergoing antibiotic treatment for bronchiectasis exacerbations at Starship Children’s Hospital and outpatient clinics. Sputum and nasal swabs were taken before and after antibiotic treatment. Sample DNA was extracted, then bacterial 16S rRNA genes amplified and sequenced via Illumina MiSeq. Results Thirty patients were recruited into this study with 81 samples contributing to the final dataset, including 8 patients with complete sets of upper and lower airway samples at both (before and after antibiotics) timepoints. Changes in alpha-diversity over the course of an exacerbation and treatment were non-significant. However, sample composition did alter over the course of an exacerbation, with most notably a reduction in the relative abundance of amplicon sequence variants assigned to Haemophilus. Discussion Haemophilus has been associated with more severe symptoms in respiratory infections and a reduction in its relative abundance may represent a positive shift in a patient’s microbiota. Current treatments for bronchiectasis may preserve bacterial diversity while altering microbiota composition.